(untitled) (Annual of the Faculty of Philosophy in Skopje, 2017)
The article offers a brief outline of some aspects of the origins of evil in several religious traditions, examining concepts of dualism and the opposition of good and evil, as both an explication of how or why evil emerged, and an attempt at exculpation of sin in human behaviour. Evil incarnate (in the form of outcast angels, demons, and the devil) is shown as originating in a celestial setting, a product of God, an impediment or an adversarial agent, an active, intentional malignant foe, a trickster and a tempter, and an enemy to God’s goodness. In order to tackle some variants of the concept of evil incarnate, examples from the Old Testament are shown, as well as from two Qumran Scrolls and the Ethiopie Book of Enoch (The Book of the Watchers). The beliefs in evil spirits lingering in the world, spreading chaos, desperation and calamity, and causing poor moral judgments in people are briefly examined as seen by some church fathers and dignitaries, reaching the stance that blaming evil incarnate (demons, devils) for wrong-doing seems ever-present, while doing nothing to truly exculpate human sinners.